Model Pentahelix dalam Pengembangan Eduwisata Berbasis Agro-Culture Di Kawasan Desa Penyangga TNBTS (Studi Di Desa Tosari, Kabupaten Pasuruan dan Desa Sapikerep, Kabupaten Probolinggo) - Novy Setia Yunas; Susanti, Anik; Nadya Izana, Nyimas; Widyawati, Wiwit (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2023)
Tosari and Sapikerep villages are two villages in the TNBTS area which are included as one of the priority areas in Indonesia. Nature tourism or agro-tourism and cultural tourism are the characteristics of the two villages. Thus, Agro-Cultural based Edutourism is one of the potential developments in the village area. The pentahelix development model is considered appropriate because it is known that the two villages collaborate with 5 roles, namely government, private sector, academia, mass media, and the community. This article is the result of research conducted for 2 months using a qualitative method with data collection techniques through in-depth interviews, focus group discussions, and observations, where research was conducted to fully describe how the pentahelix collaboration pattern occurred. As a result, the role of various actors in the pentahelix collaboration model is quite optimal. From a regulatory perspective, the central government and regional governments have shown their role where basically the two villages have become part of the tourism priority villages which in terms of infrastructure are maximally supported by the central government. As well as with regard to licensing, it is very easy to take care of development permits and public facilities that support tourism businesses and make it easier for tourists. From the private sector, many companies and investors started arriving to work together in the two villages, through their Corporate Social Responsibility pattern. On the other hand, the media also plays an important role in efforts to introduce tourism potential so that it is more widely known by tourists, while academics work together in terms of planning that is in accordance with science, as well as the active role of the community which turns out to be open and mutually willing to build villages.